Flipping an engineering mathematics classroom for a large undergraduate class - Gullayanon, Rutchanee (My University, 2015)
Although flipping classroom is not a new idea in education, implementing flipped class is somewhat a new trend. Flipping classrooms involve students in using their textbooks, online materials, and other useful resources before coming to class. Consequently, students can spend valuable class meetings on problem-solving activities instead of lectures. Positive feedback from utilizing the flipped classroom techniques has been reported in several papers. This article presents an attempt to implement the flipped classroom for a large introductory engineering class in multivariable calculus at King Mongkut's Institute of Technology Ladkrabang. The results from implementing the flipped classroom both quantitatively and qualitatively showed a higher performance and more positive feedback when compared to those obtained from this class taught by the same instructor using the traditional classroom format in the previous year.
Keywords: engineering mathematics; flipped classroom; large classroom